Nasi Babat Pegirian Surabaya Laris: Apakah karena Kualitas Produk atau Online Customer Review? - Reffli Azriel, Harista; Perwitasari, Astri Wening; Sari, Lisa Risfana; Wardhana, Aditya Narendra (Teewan Journal Solutions, 2025)
This research aims to examine the influence of product quality and online customer reviews (OCR) on social media on purchasing decisions for Nasi Babat Pegirian Surabaya. This research is quantitative research using purposive sampling techniques. We collected the data using a questionnaire assisted by Google Forms. This research received 121 responses from Nasi Babat Pegirian Surabaya consumers with the criteria of having previously purchased Nasi Babat Pegirian Surabaya and having seen online reviews about Nasi Babat Pegirian Surabaya on social media. The data analysis methods used are multiple linear regression analysis consisting of t test, F test and coefficient of determination test. The results of the t test show that product quality variables partially do not influence purchasing decisions and online customer reviews partially influence purchasing decisions. The results of the F test show that product quality and online customer reviews simultaneously influence purchasing decisions with a coefficient of determination of 58%.